Identification and measurement of fibers in scanning electron microscopy images using a high-order correlation process - Azimi-Sadjadi, Mahmood R., author; Yáñez-Suárez, Oscar, author; IEEE, publisher (Colorado State University. Libraries, 1999)
This work describes the development of a dedicated system capable of identifying, measuring and counting various types of fibers and other objects in digitized scanning electron micrograph (SEM) imagery. The system uses a recursive high order correlation (HOC) process to extract the corner pixels of the fibers. The objects are defined by grouping connected corners, so that morphometric analysis can be performed. The method developed performs satisfactorily when the density of fibers per image ranges from low to medium. Simulation results for several cases are presented, along with a discussion on the capabilities and limitations of the current version of the system.
Keywords: measurement technology; image analysis; fiberglass identification